2021
DOI: 10.1016/j.vaccine.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination adjuvated against hepatitis B in Spanish National Healthcare System (SNS) workers typed as non-responders to conventional vaccines

Abstract: An interventional, phase 4, single group assignment, without masking (open label), preventive clinical trial was carried out in health workers with biological risk in their tasks, who have been filed as non-responders to conventional vaccination against Hepatitis B. Methods: 67 health workers with biological risk in their tasks, who have been filed as non-responders to conventional vaccination against Hepatitis B, were enrolled in the Clinical Trial. All participants were from 18 years up to 64 years old. Incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In Spain, a research study similar to this one can be found in the literature that sought to demonstrate the efficacy of the adjuvanted vaccine and support its inclusion in the vaccine calendar of nonresponsive health personnel [23]. In said article, the same population group was targeted for the testing of the Fendrix ® vaccine, with similar vaccination schedules and conditions to our own.…”
Section: Discussionmentioning
confidence: 98%
“…In Spain, a research study similar to this one can be found in the literature that sought to demonstrate the efficacy of the adjuvanted vaccine and support its inclusion in the vaccine calendar of nonresponsive health personnel [23]. In said article, the same population group was targeted for the testing of the Fendrix ® vaccine, with similar vaccination schedules and conditions to our own.…”
Section: Discussionmentioning
confidence: 98%